QbD approached comparison of reaction mechanism in microwave synthesized gold nanoparticles and their superior catalytic role against hazardous nirto‐dye. (18th July 2019) - Alam, Md Sabir; Javed, Md Noushad; Pottoo, Faheem Hyder; Waziri, Aafrin; Almalki, Faisal A.; Hasnain, Md Saquib; Garg, Arun; Saifullah, Md Khalid
Abstract : Microwave irradiation (MI) process characteristically enables extremely rapid "in‐core" heating of dipoles and ions, in comparison to conventional thermal (conductance) process of heat transfer. During the process of nanoparticles synthesis, MI both modulates functionality behaviors as well as dynamic of reaction in favorable direction. So, MI providing a facile, favorable and alternative approach during nanoparticles synthesis nanoparticles with enhanced catalytic performances. Although, conventionally used reducing and capping reagents of synthetic origin, are usually environmentally hazardous and toxic for living organism. But, in absence of suitable capping agent; stability, shelf life and catalytic activity of metallic nanoparticles adversely affected. However, polymeric templates which emerged as suitable choice of agent for both reducing and capping purposes; bearing additional advantages in terms of catalyst free one step green synthesis process with high degree of biosafety and efficiency. Another aspect of current works was to understand role of process variables in growth mechanism and catalytic performances of microwave processed metallic nanoparticles, as well as comparison of these parameters with conventional heating method. However, due to poor prediction ability with previously published architect OFAT (One factor at a time) design with these nanoparticles as well as random selection of process variables with their different levels, such comparison couldn't be possible. Hence, using gum Ghatti (Anogeissus latifolia) as a model bio‐template and under simulated reaction conditions; architect of QbD design systems were integrated in microwave processed nanoparticles to establish mechanistic role these variables. Furthermore, in comparison to conventional heating; we reported well validated mathematical modeling of process variables on characteristic of nanoparticles as well as synthesized gold nanoparticles of desired and identical dimensions, in both thermal and microwave‐based processes. Interestingly, despite of identical dimension, MI processed gold nanoparticles bearing higher efficiency (kinetic rate) against remediation of hazardous nitro dye (4‐nitrophenol), into safer amino (4‐aminophenol) analogues. Abstract : Rapid "in‐core" heating of dipoles and ions by microwave irradiation (MI) modulated functionality and dynamic (reducing and capping) behavior of gum Ghatti (Anogeissus latifolia) bio‐template for favorable forward favorable kinetics during green synthesis of gold nanoparticles of high Zeta potential, low particle size and narrow size distribution index. Subsequently, in comparison to conventional thermal method, MI processed nanoparticles also favored relatively higher catalytic performances with toxic 4‐Nitrophenol dye reduction into safer 4‐ Aminophenol analogue.